Tarekat and Politics in Indonesia: Contested Authority between Murshids in the Tarekat Qadiriyah wa Naqsyabandiyah in East Java - Mukhammad Zamzami; Fikri Mahzumi; Abd A'la (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2022)
This article scrutinizes the dynamics between tarekat and politics in contemporary Indonesia in relation to the contested authority between murshids in the Tarekat Qadiriyah wa Naqsyabandiyah (TQN) in East Java. Using a historical approach, this article analyzes the position, characteristics, and political attitudes of the murshid in Jombang and Surabaya amidst the political currents during the New Order era. This article finds that murshids show adaptation and innovation in responding to challenges in their tarekat hierarchy and political leadership in Indonesia. The political stance of the murshid is considered a rational choice. In East Java, some murshids such as KH. Musta‘in Romli, KH. Adlan Ali, and KH. Usman al-Ishaqi developed different relationships with political organizations. Kiai Musta‘in tried to be adaptive and compromising as he involved in practical politics and joining the ruling party, i.e., Golkar. Kiai Adlan, on the contrary, kept his distance from the ruling regime by joining the Islamic United Development Party (Partai Persatuan Pembangunan/PPP). Kiai Usman, on the other side, remained loyal to the tarekat spirit as he refused to be involved in politics. The difference in political attitudes among the members of TQN has been considered a reflection of the political ijtihād of the murshids. Competition for authority, which resulted in conflict and internal divisions in this tarekat, is a logical consequence of political interests when they meet the tarekat and influence its dynamics.